Benefits of Project Management to Realizing Sustainable Buildings - Oday M. A. Abdullah; Umut H. İNAN and Al-Hadidy A.I. (International Journal of Engineering and Management Research, 2021)
Sustainable materials are becoming popular worldwide in terms of ecologically friendly structures that deal with pollution controls, climate change, global temperature increase, and resource conservation issues. Consequently, the researchers believe that simply using sustainable materials to design and create a building is insufficient. This article discusses several elements of sustainable construction planning including site choice mostly through the proposed project, material classification mostly through the life cycle, analysis time, cost, and commodity controls, reliability and stability, occupant health, manufacturing methodologies and procedures, and design concepts based on advanced ideas. The article argues that by integrating the choice of building components and construction strategic planning practices into the project, the productivity and consequently the reliability of the building could be significantly improved. The article also discusses the advantages and requirements of sustainable construction, the managerial roles in construction procedure, management processes, and a correlation of conventional construction planning and sustainable project management. The research paper indicates that the objective of constructing an environmentally friendly building is simply fully done when the notion of sustainability is integrated into every phase of the construction approach and that the procedures are not restricted to using recycled practices.